Evidence that short-period AM CVn systems are diverse in outburst behaviour. Issue 4 (11th February 2021) - Duffy, C; Ramsay, G; Steeghs, D; Dhillon, V; Kennedy, M R; Mata Sánchez, D; Ackley, K; Dyer, M; Lyman, J; Ulaczyk, K; Galloway, D K; O'Brien, P; et al.
ABSTRACT: We present results of our analysis of up to 15 yr of photometric data from eight AM CVn systems with orbital periods between 22.5 and 26.8 min. Our data have been collected from the GOTO, ZTF, Pan-STARRS, ASAS-SN, and Catalina all-sky surveys and amateur observations collated by the AAVSO. We find evidence that these interacting ultracompact binaries show a similar diversity of long-term optical properties as the hydrogen accreting dwarf novae. We found that AM CVn systems in the previously identified accretion disc instability region are not a homogenous group. Various members of the analysed sample exhibit behaviour reminiscent of Z Cam systems with long superoutbursts (SOs) and standstills, SU UMa systems with regular, shorter SOs, and nova-like systems that appear only in a high state. The addition of TESS full frame images of one of these systems, KL Dra, reveals the first evidence for normal outbursts appearing as a precursor to SOs in an AM CVn system. Our results will inform theoretical modelling of the outbursts of hydrogen deficient systems.